The effect of an antibiotic stewardship program on tigecycline use in a Tertiary Care Hospital, an intervention study - Rima Moghnieh; Dania Abdallah; Lyn Awad; Marwa Jadayel; Nicholas Haddad; Hani Tamim; Aline Zaiter; Diana-Caroline Awwad; Loubna Sinno; Salam El-Hassan; Rawad Lakkis; Rabab Khalil; et al. (BMC, 2020)
Abstract Background A drug-oriented antibiotic stewardship intervention targeting tigecycline utilization was launched at Makassed General Hospital, Beirut, Lebanon, in 2016 as a part of a comprehensive Antibiotic Stewardship Program (ASP). In this study, we evaluated the effect of this intervention on changing tigecycline prescription behavior in different types of infections, patient outcome and mortality, along with tigecycline drug use density, when compared to an earlier period before the initiation of ASP. Methods This is a retrospective chart review of all adult inpatients who received tigecycline for more than 72 h between Jan-2012 and Dec-2013 [period (P) 1 before ASP] and between Oct-2016 and Dec-2018 [period (P) 2 during ASP]. Results Tigecycline was administered to 153 patients during P1 and 116 patients during P2. The proportion of patients suffering from cancer, those requiring mechanical ventilation, and those with hemodynamic failure was significantly reduced between P1 and P2. The proportion of patients who received tigecycline for FDA-approved indications increased from 19% during P1 to 78% during P2 (P < 0.001). On the other hand, its use in off-label indications was restricted, including ventilator-associated pneumonia (26.1% in P1, 3.4% in P2, P < 0.001), hospital-acquired pneumonia (19.6% in P1, 5.2% in P2, P = 0.001), sepsis (9.2% in P1, 3% in P2, P = 0.028), and febrile neutropenia (15.7% in P1, 0.9% in P2, P < 0.001). The clinical success rate of tigecycline therapy showed an overall significant increase from 48.4% during P1 to 65.5% during P2 (P = 0.005) in the entire patient population. All-cause mortality in the tigecycline-treated patients decreased from 45.1% during P1 to 20.7% during P2 (P < 0.0001). In general, mean tigecycline consumption decreased by 55% between P1 and P2 (P < 0.0001). Conclusion The drug-oriented ASP intervention targeting tigecycline prescriptions improved its use and patient outcomes, where it helped curb the over-optimistic use of this drug in off-label indications where it is not a suitable treatment option.